Learner autonomy dimensions: What motivated and unmotivated EFL students think - Gamble, Craig; Wilkins, Michael; Aliponga, Jonathan; Koshiyama, Yakuko; Yoshida, Keiko; Ando, Shirley (Lingua Posnaniensis, 2018)
To counter the misunderstandings that students from East Asian countries like Japan are less autonomous than learners from other cultural backgrounds, this exploratory research examined Japanese university students’ attitudes toward their own responsibility and ability to study English autonomously. Student motivation was observed specifically to determine how students perceived their learning inside and outside the classroom. In this study, 958 students from 12 universities across Japan participated in a 24-item adapted questionnaire on learner autonomy. Based on the data collected, slight to not significant differences were revealed regarding students’ perceptions of responsibility to perform autonomous learning tasks. However, with regard to perceived ability to perform autonomous learning tasks, there were significant differences as motivated students demonstrated a far greater confidence in their capacity to be involved in their own learning than unmotivated students, yet they did not necessarily act on their ability to do so. These findings and their implications are explored and discussed.